Aitken nuclei sonde with constant expansion ratio irrespective of ambient pressure - Ito, Tomoyuki; Ikegami, Miwako; Kanazawa, Izuo (1983)
P(論文) A new type of Aitken nuclei sonde is reported. The sonde consists of an expansion fog chamber, which is similar in principle to the Pollak counter or the Aitken counter, as a measuring device of Aitken unclei concentration. The most important characteristics of the present fog chamber are that it is a very compact automatic one and it has a construction to keep expansion ratio constant irrespective of ambient pressure. The constant expansion ratio is an essential requirement for the measurement of Aitken nuclei concentration at different heights by a balloon or an airplane. The variation of measured values during 50 times measurement for a same air sample is smaller than 3% of the mean. Two identical fog chambers in the present sonde give Aitken unclei concentrations which agree within 50(cm)^<-3> for the concentration range covering between about 200 and about 2000cm^<-3>. A nuclei measuring signal is inserted into rawinsonde signal, which is transmitted to a ground station, every minute for 10s. The total weight of a sonde is 9kg, comprising a 5kg fog chamber, a 3.5kg battery and a 0.5kg rawinsonde. departmental bulletin paper